The association between CKD-associated pruritus and quality of life in patients undergoing hemodialysis in Pakistan - Rehman, Inayat Ur; Chan, Kok Gan; Munib, Syed; Lee, Learn Han; Khan, Tahir Mehmood (Lippincott, Williams & Wilkins, 2019)
Chronic kidney disease (CKD)-associated pruritus is one of the most common symptoms found in patients who undergo dialysis for CKD, leading to a compromised quality of life. This study aimed to investigate the association between CKD-associated pruritus and the quality of life in patients undergoing hemodialysis in Pakistan. A cross-sectional multicenter study was carried out from July 2016 to April 2017 in 2 tertiary care hospitals in Pakistan. Patients aged 18 years and above of both genders, undergoing hemodialysis, understood the Urdu language, and were willing to participate; were included. Of 354 recruited patients with a response rate of 100%, majority (66.1%) of the patients were males. The median (intra-quartile range [IQR]) age of patients was 42.0 [34.0-50.0] years. The prevalence of pruritus was 74%. The median [IQR] score for pruritus was 10.0 (out of possible 25) [8.0-12.0]. Multivariate linear regression revealed a statistically significant association between CKD-associated pruritus with age of patients (β=0.031; 95% confidence interval [CI]=0.002-0.061; P=.038), duration of CKD (β=-0.013; 95% CI=-0.023 - 0.003; P=.014) and quality of life (β= -0.949; 95% CI=-1.450; -0.449). The median [IQR] score for health-related quality of life was 52.00 [43.00-58.00].Prevalence of CKD-associated pruritus was reported to be 74% and it negatively affected the patient's quality of life. Patients with moderate to severe CKD-associated pruritus have poor quality of life. With an increase in intensity of pruritus, the QOL score decreased among the patients undergoing hemodialysis. Copyright © 2019 the Author(s).